Предмет: Алгебра,
автор: svyatoylord
Даю 20 баллов за номер 1143.
Приложения:
Ответы
Автор ответа:
0
a (там опечатка ,должно стоять -(c-x)^-2
1)(c-x)²-1/(c-x)²=[(c-x)^4-1]/(c-x)²=[(c-x)²-1]*[(c-x)²+1]/(c-x)²
2)[(c-x)²-1]*[(c-x)²+1]/(c-x)²:[(c-x)²-1]=[(c-x)²-1]*[(c-x)²+1]/(c-x)²*[(c-x)²-1]=
=[(c-x)²+1]/(c-x)²
3)[(c-x)²+1]/(c-x)²-1/(c-x)²=[(c-x)²+1-1]/(c-x)²=(c-x)²/(c-x)²=1
б (
в знаменателе должно стоять (c-x)²(c^4+c²x²+x^4)^-1
1)3/(c²+cx+x²)-1/(c²-cx+x²)=(3c²-3cx+3x²-c²-cx-x²)/[(c²+cx+x²)(c²-cx+x²)]=
=(2c²-4cx+x²)/(c^4-c³x+c²x²+c³x-c²x²+cx³+c²x²-cx³+x^4)=
=2(c²-2cx+x²)/(c^4+c²x²+x^4)=2(c-x)²/(c^4+c²x²+x^4)
2)2(c-x)²/(c^4+c²x²+x^4):(c-x)²/(c^4+c²x²+x^4)=2
1)(c-x)²-1/(c-x)²=[(c-x)^4-1]/(c-x)²=[(c-x)²-1]*[(c-x)²+1]/(c-x)²
2)[(c-x)²-1]*[(c-x)²+1]/(c-x)²:[(c-x)²-1]=[(c-x)²-1]*[(c-x)²+1]/(c-x)²*[(c-x)²-1]=
=[(c-x)²+1]/(c-x)²
3)[(c-x)²+1]/(c-x)²-1/(c-x)²=[(c-x)²+1-1]/(c-x)²=(c-x)²/(c-x)²=1
б (
в знаменателе должно стоять (c-x)²(c^4+c²x²+x^4)^-1
1)3/(c²+cx+x²)-1/(c²-cx+x²)=(3c²-3cx+3x²-c²-cx-x²)/[(c²+cx+x²)(c²-cx+x²)]=
=(2c²-4cx+x²)/(c^4-c³x+c²x²+c³x-c²x²+cx³+c²x²-cx³+x^4)=
=2(c²-2cx+x²)/(c^4+c²x²+x^4)=2(c-x)²/(c^4+c²x²+x^4)
2)2(c-x)²/(c^4+c²x²+x^4):(c-x)²/(c^4+c²x²+x^4)=2
Автор ответа:
0
а квадратные скобки это что???
Похожие вопросы
Предмет: Математика,
автор: pasaantonik
Предмет: Алгебра,
автор: uteganov2006
Предмет: Информатика,
автор: limv40
Предмет: Обществознание,
автор: Puzima12345
Предмет: Биология,
автор: Эльвира1243